Epithelial-Mesenchymal Plasticity in Cancer Progression and Metastasis - Lu, Wei; Kang, Yibin (Developmental cell, 2019)
Epithelial-to-mesenchymal transition (EMT) and its reversed process, mesenchymal-to-epithelial transition (MET), are fundamental processes in embryonic development and tissue repair but confer malignant properties to carcinoma cells, including invasive behavior, cancer stem cell activity, and greater resistance to chemotherapy and immunotherapy. Understanding the molecular and cellular basis of EMT provides fundamental insights into the etiology of cancer and may, in the long run, lead to new therapeutic strategies. Here, we discuss the regulatory mechanisms and pathological roles of epithelial-mesenchymal plasticity, with a focus on recent insights into the complexity and dynamics of this phenomenon in cancer.